CRUSTAL AND UPPER MANTLE STRUCTURE IN THE EASTERN PART OF THE KAMCHATKA PENINSULA FROM P-WAVE RECEIVER FUNCTIONS - M. A. Khritova; V. V. Mordvinova; E. A. Kobeleva (Геодинамика и тектонофизика, 2025)
The paper deals with the study of the deep structure of the Earth’s crust and upper mantle in the eastern part of the Kamchatka Peninsula. One-dimensional sections have been constructed to illustrate the relationship between shear wave velocity VS and depth h, obtained by inversion of longitudinal receiver functions, computed from seismograms of distant earthquakes recorded at 11 seismic stations of the KB FRC GS RAS for the period 2011–2016. The study presents a two-dimensional VS-model to a depth of 70 km for a profile along the 950-km East Kamchatka volcanic belt.The constructed sections reveal a layered structure of the crust and ~40 km of the subcrustal mantle, which can roughly be described as a layered-block structure. The following structural layers are distinguished within the Earth’s crust: contrasting boundary at a depth of 5–7 km with a 2.8 to 3.2 km/s leap in transverse wave velocity; homogeneous layer at a depth of 10–25 km with a smooth VS increase from 3.5 to 3.7 km/s; transitional crust-mantle zone at a depth of 28–36 km with VS=3.8–3.9 km/s. The upper mantle layers are referred to as low velocity layers (VS=4 km/s) relative to IASP91 global model. The velocity profile from the Avacha Bay area reveals a complex crustal structure; velocity anomalies found at depths of up to 25 km are most likely a reflection of the Petropavlovsk-Malki zone of transverse dislocations, which is the conditional boundary between the structures of Southern and Central Kamchatka.